Examen especial a la gestión de talento humano del gobierno autónomo descentralizado parroquial rural de zurmi del cantón nangaritza, provincia zamora chinchipe, periodo 2014 - Troyani Betancourt, Mayra Yadira (2016)
This research is themed Special to the management of human talent of the Vestry of Zurmi Canton Nangaritza Examination, during the period January 1 to December 31, 2014, was performed to meet the requirement, prior decide the degree of graduates Accounting and Auditing, its objectives were directed to apply tests and special examination techniques to obtain evidence to support the final report to determine the degree of strength and fairness of the management performed. The project objectives were successfully met, the methodological process used in this study was developed based on basic and fundamental concepts related to the special examination process from planning to communicating results, internal control and evaluation, among other materials that allowed the development of fieldwork of this investigation. After analyzing and synthesizing bibliographic references, with the permission of the directors of the Vestry of Zurmi he proceeded to the inspection of documents and other sources of accounting to determine the risk and the approach of special consideration; then by applying test work performed by human talent under study and submitted a report containing comments, conclusions and recommendations designed to assist in decision-making for improving the administration and development of the activities were analyzed.